2021
DOI: 10.2138/am-2021-7581
|View full text |Cite
|
Sign up to set email alerts
|

P-V-Tmeasurements of Fe3C to 117 GPa and 2100 K: Implications for stability of Fe3C phase at core conditions

Abstract: This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America. The published version is subject to change. Cite as Authors (Year) Title. American Mineralogist, in press.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 60 publications
2
12
0
Order By: Relevance
“…On the other hand, Mashino et al [156] reported the Fe 3 C phase as a liquidus phase in their melting experiments in the Fe-C system to 203 GPa, but placed the possible occurrence of reaction (R2) at 255 GPa from chemical and textural analyses of recovered samples (Figure 29b). McGuire et al [169] made thermodynamic calculations on the P-T locations of reaction (R2) using their newly established EoS for Fe 3 C. The reaction is located at 87 GPa and 300 K and 251 GPa and 3000 K and its boundary is consistent with the results of both Tateno et al [23] and Mashino et al [156] (Figure 29b).…”
Section: • Thermodynamic Model Of the Systemsupporting
confidence: 62%
See 4 more Smart Citations
“…On the other hand, Mashino et al [156] reported the Fe 3 C phase as a liquidus phase in their melting experiments in the Fe-C system to 203 GPa, but placed the possible occurrence of reaction (R2) at 255 GPa from chemical and textural analyses of recovered samples (Figure 29b). McGuire et al [169] made thermodynamic calculations on the P-T locations of reaction (R2) using their newly established EoS for Fe 3 C. The reaction is located at 87 GPa and 300 K and 251 GPa and 3000 K and its boundary is consistent with the results of both Tateno et al [23] and Mashino et al [156] (Figure 29b).…”
Section: • Thermodynamic Model Of the Systemsupporting
confidence: 62%
“…The figure is from [156]. Takahashi et al [167]; McGuire et al [169]). The solid red line shows reaction Fe 3 C = Fe 7 C 3 +Fe calculated in [169].…”
Section: Figure 28mentioning
confidence: 99%
See 3 more Smart Citations